Emotional Intelligence and Venture Performance. (8th February 2017) - Ingram, Amy; Peake, Whitney Oliver; Stewart, Wayne; Watson, Warren
Abstract : Scholars emphasize the importance of emotion in entrepreneurship and the potential of emotional intelligence, but research is sparse in the field. We develop and test a novel partial mediation model of emotional intelligence, interpersonal processes, and venture performance. The results indicate that interpersonal emotional skills, which entail the recognition and management of emotions in others, has a direct effect on venture performance, but intrapersonal emotional skills pertaining to self‐awareness and regulation of emotions do not. Additionally, both the intrapersonal and interpersonal dimensions of emotional intelligence have an indirect influence on firm performance via interpersonal processes that entail functioning in key activities within the firm. We discuss the implications and address potential avenues for future research on this important topic.